A Pilot Study on the Effect of Added Sugar on Response Inhibition: Event-Related Potentials in a Go/NoGo Task - Karolina Jocbalyte; Rytis Stanikunas (Medicina, 2025)
Background and Objectives: Added sugar usage has become an important public health issue nowadays. Therefore, the interest in studying the cognitive and emotional effects associated with sugar consumption has increased. The present study aimed to investigate how the intake of added sugar affects participants’ impulsivity and cognitive functions monitored during the performance of a computerized Go/NoGo task. Materials and Methods: This study included 20 subjects (10 men and 10 women). Quantitative data for this study were collected via self-report questionnaires, including demographics, the Dietary Fat and Free Sugar—Short Questionnaire (DFS), the Yale Food Addiction Scale (YFAS 2.0), and the Barratt impulsiveness scale-11 (BIS-11). Results: Event-related potentials (ERPs) were registered throughout this study. Comparing the results of psychophysiological and neuropsychological evaluations before and after the added sugar consumption reveals differences in ERPs. Specifically, the NoGo-P3 amplitude increased after the intake of added sugar. However, there were no behavioral differences between the two experimental sessions. Conclusions: Overall, the results of our study suggest that added sugar intake was associated with stronger neuronal firing in NoGo trials. One possible explanation for this could be the need for more cognitive endeavors for participants to successfully inhibit their response impulses after added sugar consumption.